1978
DOI: 10.1159/000214228
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and Coagulation Impairment after Portacaval Shunt in the Rat

Abstract: A study has been performed to evaluate the effect of the portacaval shunt on some coagulation tests in the rats. Thrombocytopenia develops, accompanied by a decrease in the total protein and fibrinogen concentrations. Moreover, the Quick time is lengthened, whereas the partial thromboplastin time is not modified. The maximal amplitude and elasticity of the clot, recorded by thrombelastography, appear reduced, and k is lengthened. The results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Experiments with washed platelets might be useful to clarify this point, but the rather small quantity of blood which can be collected from a shunted rat creates technical difficulties. At the present, the only sure datum is that the platelet population is lowered (13), probably owing to the deranged activity of the bone marrow (8), indicating a general depression of haemopoiesis. The implication is that, as the platelet production is reduced, there is a large population of old platelets in circulation which are known to have a decreased reactivity to aggregating agents (15,16,20) and clot retraction ability (7).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Experiments with washed platelets might be useful to clarify this point, but the rather small quantity of blood which can be collected from a shunted rat creates technical difficulties. At the present, the only sure datum is that the platelet population is lowered (13), probably owing to the deranged activity of the bone marrow (8), indicating a general depression of haemopoiesis. The implication is that, as the platelet production is reduced, there is a large population of old platelets in circulation which are known to have a decreased reactivity to aggregating agents (15,16,20) and clot retraction ability (7).…”
Section: Discussionmentioning
confidence: 83%
“…We attributed the phenomena to the alterations occurring in plasma which had some conse quences on the platelet function. In fact, we found that the total protein and the fibrinogen concentrations were reduced in the shunted rats and that there was blood hypocoagulability (13). Cirrhotic patients in which the liver function was strongly impaired presented coagulation defects (4,21,24,25,27) and en hanced spontaneous fibrinolytic activity (2,14,17).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation